Lithuanian self goverment and german occupation government: between collaboration and resistance. - Jegelevičius, Sigitas (Genocidas ir rezistencija, 2000)
There were at least five anti–Nazi resistance movements in Lithuania during the Nazi occupation: the Lithuanian, the Polish, the Jewish, the pro–Soviet and the Soviet. They differed not only in their national orientation but also in state political orientation. Undoubtedly, both during the war and now, the Lithuanian resistance movement is the most important one for us, because it preserved the idea of the Lithuanian state. It should also be noted that the Lithuanians did not have their own government in exile anywhere during the war. The Soviet puppet government, which resided in Penza and later in Moscow, was not the government of the Lithuanian state. All these elements were, and still are, decisive in assessing the role of Lithuanian self–government during the Nazi occupation. In assessing the role of the Lithuanian self–government and its place and significance in the Lithuanian anti–Nazi resistance, we are eager to take the Lithuanian anti–Soviet June Uprising and its consequences as our starting point.